The great escape? SARS-CoV-2 variants evading neutralizing responses - Prévost, Jérémie (Cell Host Microbe, 2021)
In the latest issues of Cell Host & Microbe and Cell, three articles describe new mutations in the SARS-CoV-2 Spike receptor binding domain that escape neutralizing responses. These highlight the importance of surveillance of SARS-CoV-2 evolution to anticipate and manage new variants that could impact reinfection, vaccine efficacy, and immunotherapies.